Regulating the manufacturing, distribution and selling of vape in Malaysia / Nor Aqilah Hassim - Hassim, Nor Aqilah (2018)
The usage of vape is a global phenomenon. It has been the subject of a public health dispute. There are many issues relating to vape and Malaysia has yet to regulate it. This study investigates the issues and challenges in regulating the manufacturing, distribution and selling of vape in Malaysia. This include the assessment of current legal position in manufacturing, distribution and selling of vape in Malaysia and highlighting its strength and weaknesses. Thereafter, this study determines the possible reform to the current legal positions in Malaysia in regulating the manufacturing, distribution and selling of vape. A mixed method was adopted with the combination of doctrinal, qualitative and comparative research methodology. The study shows that there are no regulations in Malaysia governing vape. The only provision available relating to vape, is the nicotine, that is governed under the Poison Act 1952. However, this research shows that Poison Act 1952 is too rigid in governing nicotine used in vape because nicotine under this Act is for medicinal purpose. Therefore, amendments need to be done to regulate vape as a commercial product under the Control of Tobacco Product Regulation 2004 and not as a medicinal product under the Poison Act 1952. The regulations of vape must take into consideration the balancing between the public health interest and economy’s impact.